PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 115482 PEKAN MARBAU - Rahma Hidayani; Zainuddin M.; Winara; Sri Mustika Aulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research departs from learning problems which are still dominated by lecture methods from teachers, while the space for students to be actively involved in the classroom is still very limited which results in low student learning outcomes. Seeing these conditions, the use of the Creative Problem Solving (CPS) learning model is one of the learning models that is considered relevant and able to answer these challenges. The purpose of this study is to describe the extent of the effectiveness of the application of the CPS model in influencing student learning outcomes, especially in science subjects. The research approach implemented in this study relies on experimental methods with the adoption of quantitative research. The researcher established the design of a one-group pretest-posttest as the core plan. Based on the results of the data processing that has been carried out, the average grade score obtained by grade V students of SD Negeri 115482 Pekan Marbau before the treatment (pre-test) is 59.4. Drastic changes emerged after the CPS model was implemented, where the average post-test score shot up to 81.2 with a standard deviation of 7.26 and a difference of profit of 21.8 points. Researchers can conclude that the use of the Creative Problem Solving (CPS) model has been proven to have a positive and very meaningful impact on improving the learning outcomes of social studies of grade V students at SD Negeri 115482 Pekan Marbau for the 2025/2026 Academic Year.